CD4+ T Cell Fate Decisions Are Stochastic, Precede Cell Division, Depend on GITR Co-Stimulation, and Are Associated With Uropodium Development - Cobbold, Stephen P.; Adams, Elizabeth; Howie, Duncan; Waldmann, Herman (Frontiers in Immunology, 2018)
During an immune response, naïve CD4+ T cells proliferate and generate a range of effector, memory and regulatory T cell subsets, but how these processes are co-ordinated remains unclear. A traditional model suggests that memory cells use mitochondrial respiration and are survivors from a pool of previously proliferating and glycolytic, but short-lived effector cells. A more recent model proposes a binary commitment to either a memory or effector cell lineage during a first, asymmetric cell division, with each lineage able to undergo subsequent proliferation and differentiation. We used improved fixation and staining methods with imaging flow cytometry in an optimised in vitro system that indicates a third model. We found that cell fates result from stochastic decisions that depend on GITR co-stimulation and which take place before any cell division. Effector cell commitment is associated with mTORC2 signalling leading to uropodium development, while developing memory cells lose mitochondria, have a nuclear localization of NFkB and depend on TGFbeta for their survival. Induced, T helper subsets and foxp3+ regulatory T cells were found in both the effector and memory cell lineages. This in vitro model of T cell differentiation is well suited to testing how manipulation of cytokine, nutrient other components of the microenvironment might be exploited for therapeutic purposes.